IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA KEMAMPUAN PEMECAHAN MASALAH MATERI PECAHAN KELAS V SEKOLAH DASAR - Lestari, Siti Puji; Sary, Ryky Mandar; Sukamto, Sukamto (Universitas PGRI Semarang, 2019)
Implementation of Problem Based Learning Models on Mathematical Problem Solving Capabilities of Elementary School Class V Fractions. The objectives to be achieved in this study are to determine the implementation of Problem Based Learning models in the mathematical problem solving ability of fraction material for fifth grade students of elementary schools and To identify whether there is an increase or not the ability to solve mathematical problems of students towards the implementation of Problem Based Learning models of fractions for students class V SDN Tlogorejo Pati. This type of research is a mixed methods research method in the form of concurrent embedded. The study population was all fifth grade students of SD Tlogorejo Pati 2019/2020 Academic Year. Samples takeere 30 fifth grade students using Nonprobability Sampling in the form of Saturated Sampling. Data collection techniques used for research instruments are tests, interviews, observations and documentation. The instruments used were validated tests by experts, interview guidelines and observation guidelines. Data in this study were obtained through interviews, tests, observations, and documentation. Based on the results of calculations using the t test obtained tcount = 30.29 with ttable = 2.001. Because tcount = 30.29 ttable = 2.001, H0 is rejected and Ha is accepted. This means that the ability to solve problems before and after treatment is not the same in grade V elementary school students. Then the results of calculations using N-Gain obtained calculation results of 0.640. These results fall into the moderate classification. So it can be concluded an increase in the ability to solve problems in fractional material gets an average increase of 0.640. This means that there is an increase in the ability to understand the problem in the Problem Based Learning model.Â